Faktor-Faktor yang Berhubungan dengan Pemberian ASI Eksklusif di RSUD Siti Fatimah Palembang Tahun 2024 - Novia Adityaningsih; Intan Sari; Sri Handayani; Putu Lusita Nati Indriani (STIKes Budi Mulia Sriwijaya, 2024)
Providing exclusive breast milk to babies is important in developing human resources from an early age, because from an early age babies receive the healthiest and most appropriate food which will have a positive influence on subsequent growth and development. The research aims to determine the factors associated with exclusive breastfeeding at Siti Fatimah Regional Hospital, Palembang in 2024. This research design uses an analytical survey with a cross sectional method. The population in this study is a population using data on the number of babies at the Siti Fatimah Hospital, Palembang in 2023, namely 285 babies. The sampling technique in this study was accidental sampling, that is, samples were taken from respondents who happened to come to the Siti Fatimah Hospital, Palembang at the time the research was carried out. . The research sample was all mothers who had children aged 7-12 months who were at the Siti Fatimah Palembang Regional Hospital at the time the research was carried out. The analysis technique uses Univariate, Bivariate (Chi square). Based on the results of the Chi Square statistical test, there is a relationship between partial employment and exclusive breastfeeding at the Siti Fatimah Regional Hospital, Palembang in 2024. The Chi-Square results obtained p value = 0.001. There is a partial relationship between partial knowledge and exclusive breastfeeding at the Siti Fatimah Palembang Regional Hospital. In 2024, the Chi-Square results obtained p value = 0.004. There was a relationship between partial family support and exclusive breastfeeding at Siti Fatimah Regional Hospital, Palembang. In 2024, the Chi-Square results obtained p value = 0.001. It is hoped that It will continue to Increase mothers' knowledge about exclusive breastfeeding by providing education about exclusive breastfeeding so that it is hoped that it can influence mothers’ attitudes towards providing exclusive breastfeeding. Providing workshops/training to health workers, especially midwives within the Siti Fatimah Regional Hospital, regarding lactation management